Measures of Racism and Discrimination in Preterm Birth Studies. Issue 1 (30th January 2023) - Balascio, Phoebe; Moore, Mikaela; Gongalla, Megha; Regan, Annette; Ha, Sandie; Taylor, Brandie D.; Hill, Ashley V.
Abstract : Studies of racism and preterm birth use inconsistent, unstandardized metrics of racial discrimination; standard measures should be developed for application in perinatal research. Abstract : OBJECTIVE: Preterm birth (any birth at less than 37 weeks of gestation) disproportionally affects Black birthing people and is associated with adverse perinatal and fetal health outcomes. Racism increases the risk of preterm birth, but standardized measurement metrics are elusive. This narrative synthesis examines literature on measures of racial discrimination used in preterm birth research. DATA SOURCES: Six databases (CINAHL, Cochrane, EMBASE, PubMed [MEDLINE], Scopus, Web of Science) and ClinicalTrials.gov were searched. Search terms were categorized into three groups (racism terms, measurement terms, preterm birth terms) to identify original research articles that explored associations between racism and preterm birth. English-language, original research articles with U.S. populations were included. METHODS OF STUDY SELECTION: Studies were excluded if conducted in only White populations, if only paternal factors were included, or if only racial differences in preterm birth were described. Articles were independently reviewed by two blinded researchers for inclusion at every stage of screening and data extraction; a third reviewer resolved discrepancies. TABULATION, INTEGRATION, AND RESULTS: Sixty studies were included in the final analysis. Articles primarily included measures examining interpersonal forms of racism (n=17) through the Experiences of Discrimination and Everyday Discrimination scales, neighborhood composition (n=22) with the Neighborhood Deprivation Index and the Index of Concentration at the Extremes, policy-level racism (n=12) through institutions such as residential racial segregation or policy inequities, or multiple forms (n=9). CONCLUSION: Among studies, assessment methods and application of constructs varied. This heterogeneity poses significant challenges to understanding associations between racial discrimination and preterm birth and to describing potential etiologic pathways of preterm birth, which ultimately hinders development of effective intervention. Strategies to capture multilevel exposures to racism require the development and expansion of metrics that are culturally inclusive, empirically valid, and reliable among Black pregnant populations. SYSTEMATIC REVIEW REGISTRATION: PROSPERO, CRD42022327484.